Puisi At-Ṭumaʻnīnah dalam Antalogi Puisi Hams Al-Jufūn Karya Mikhail Nuaimah: Analisis Semiotik Riffaterre - Hasaniyah, Nur; Zen, Regina Aulia; Hasanah, Ummi; Muhamad Husain Rifa’i; Genta Ardytama Yudha; Fares Albadr Mohammed (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
The best literary work of Mikhail Nuaimah is Hams al-Jufūn which is in the form of a poetry anthology. This work contains 44 poem titles depicting three major themes, namely personality, society, and nature. One of the poems featured in the anthology is titled At-Ṭumaʻnīnah. This study aims to examine (1) the outcomes of heuristic reading, (2) hermeneutic reading, and (3) the matrices, models, and hypograms within the poem At-Ṭumaʻnīnah by Mikhail Nuaimah through the lens of Michael Riffaterre's semiotic analysis. This literature study employs a qualitative descriptive research methodology. Data were sourced from Hams al-Jufūn by Mikhail Nuaimah. The data collection method involved reading and note-taking techniques, while data analysis was conducted using Miles and Huberman's framework, encompassing data reduction, data presentation, and conclusion drawing through systematic heuristic and hermeneutic reading techniques. The findings of this study are as follows: (1) heuristic reading reveals that the poem depicts a person's resilient home, capable of withstanding various adversities; (2) hermeneutic reading indicates that the poem narrates an individual's attainment of profound peace of mind, fortified by a strong shield to confront life's challenges and fears; (3) the matrix of this poem conveys a sense of calm, while the model represents a strong shield of the heart, underscored by faith in qada and qadar, which cultivates inner tranquility. The hypogram of this poem connects to the hadith of Imam Thabrani from Abu Umamah. Abstrak Karya sastra terbaik dari Mikhail Nuaimah ialah Hams al-Jufūn yang berbentuk Antalogi puisi. Karya ini memuat 44 judul puisi dengan menggambarkan tiga tema besar yaitu ketokohan, sosial, dan alam. Salah satu judul puisi dari antalogi tersebut adalah At-Ṭumaʻnīnah. Penelitian ini bertujuan untuk mengungkapkan bagaimana (1) hasil pembacaan heuristik,  (2) pembacaan herme-neutik, dan (3) matriks, model serta  hipogram dalam puisi yang berjudul At-Ṭumaʻnīnah karya Mikhail Nuaimah dengan analisis semiotic Michael Riffaterre. Ini adalah penelitian kepustakaan menggunakan metode penelitian deskriptif kualitatif. Data diambil dari antologi puisi Hams al-Jufun karya Mikhail Nuaimah. Metode pengumpulan data berupa teknik baca dan catat, dan analisis data menggunakan analisis Miles dan Huberman berupa reduksi data, penyajian data, dan penarikan kesimpulan melalui teknik pembacaan heuristik dan hermeneutik secara sistematis. Hasil dari penelitian ini adalah: (1) hasil pembacaan heuristik puisi ini menceritakan rumah seseorang yang kokoh, dapat menahan untuk setiap bencana yang dihadapi; (2) hasil pembacaan hermeneutik dalam puisi ini adalah menceritakan seseorang mencapai ketentraman hati yang hebat dengan tameng yang kokoh untuk menghadapi segala macam kesulitan sampai pada ketakutan hidup; (3) matriks dari  puisi  ini  adalah rasa ketenangan, model dari puisi ini adalah tameng hati yang kuat dan percaya akan qada dan qadar membuat hati menjadi penuh ketenangan, dan hipogram  dari  puisi  ini berhubungan dengan hadist Imam Thabrani dari Abu Umamah